Warsztat nauczyciela polonisty w edukacji gimnazjalnej (na podstawie analizy dokumentów zastanych) - Jastrzębska-Golonka, Danuta (Polonistyka. Innowacje, 2015)
The aim of the article is to depict and assess the chosen aspects of the Polish teacher’s technique conducted thanks to the analysis of the syllabus in the conspects, notebooks, short tests and teacher’s teaching activities. The aspects assessed there: the ways of defining the topics, the aims of the lessons, teaching methods, the ways of taking notes and exercises. The analysis proved that not only the teacher takes care of the realization of the syllabus in the junior high school but it showed that traditional teaching methods dominate as well.